1993
DOI: 10.1111/j.1439-0523.1993.tb00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Related Changes in Chlorophyll Fluorescence and Contents of Chlorophyll and Carotenoids in Andean and European Potato Clones

Abstract: Low-temperature adapted Andean potato clones and low-temperature sensitive European clones cultivated at 20/10 °C were compared during stress occurring as the result of low-temperature treatments.The stress response of leaf tissue was assessed by measuring the decrease in chlorophyll fluorescence (Fv/Fm) in detached leaves during a period of six days. After temperature stress combined with Hght Fv/Fm decreased only slightly in the Andean clones, but was markedly lower than the initial values in the European cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…1995). The freezing‐tolerant wild potato species which are able to cold acclimate, are also more tolerant to low temperature photo‐inhibition (Steffen & Palta 1986, 1989; Kristjandottir & Merker 1993; Seppänen et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1995). The freezing‐tolerant wild potato species which are able to cold acclimate, are also more tolerant to low temperature photo‐inhibition (Steffen & Palta 1986, 1989; Kristjandottir & Merker 1993; Seppänen et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The freezing-tolerant wild potato species which are able to cold acclimate, are also more tolerant to low temperature photo-inhibition (Steffen & Palta 1986Kristjandottir & Merker 1993;Seppänen et al 2001). The results indicate that improved capacity to keep Q oxidized after night frost is one of the tolerance mechanisms missing in S. tuberosum species which are unable to cold acclimate.…”
Section: Photosynthetic Responses To Night Frostsmentioning
confidence: 96%
“…Chl fluorescence provides a non-destructive, rapid means of assessing both photo-chemical quantum yield and photoinhibition (Krause 1988, Krause andWeis 1991), and has been widely employed as an indicator of plant response to stresses, especially those imposed by air and water pollution (Lichtenthaler 1988), water deficit (Cornic and Massacci 1996), high and low temperature (Kristjansdottir andMerker 1993, Willits andPeet 2001), and salinity (Smillie and Nott 1982). Larcher (1994) has suggested that it may represent the most reliable way of quantifying photosynthesis in heat-stressed plants.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used as an indicator of plant responses to stress, especially air and water pollution (Lichtenthaler 1988), water deficit in potato (Jefferies 1992, Basu et al 1998) and bread wheat (Hassan 2006), high and low-temperature in potato (Kristjansdottir and Merker 1993), sunflower and maize (Yordanov et al 1997), and tomato (Willits and Peet 2001), and salinity in sugar beet, sunflower, and bean (Smillie and Nott 1982). Larcher (1994) suggested that for monitoring heat stress, Chl fluorescence may be a more reliable measurement of photosynthesis than CO 2 exchange, which can be influenced by stomata closure not primarily induced by heat.…”
Section: Introductionmentioning
confidence: 98%